EXPERIENCE OF MULTIVISCERAL RESECTIONS IN LOCALLY ADVANCED AND PRIMARY-MULTIPLE RECTAL CANCER - S.G. AFANASYEV; I.B. KHADAGAEV; S.A. FURSOV; E.A. USYNIN; A.K. GORBUNOV; U.B. URMONOV; A.V. USOVA; A.V. AVGUSTINOVICH; A.S. TARASOVA (Avicenna Tajik State Medical University, 2020)
Objective: Assessing short-term and long-term results of multivisceral resections (MVR) performed for rectal cancer (RC) with invasion into adjacent pelvic organs, as well as the effectiveness of bladder reconstruction with the formation of a urinary reservoir of «low» pressure. Methods: The work was based on the results of surgical treatment of 37 patients with locally advanced or primary multiple RC underwent MVR. Invasion of adjacent small organs was observed in 89.2%, primary multiple malignant tumors (PMMT) - in 10.8% of patients included in the study. Results: According to the preoperative examination of tumor infiltration of one adjacent organ was diagnosed in 20 (54.1%), two or more organs - in 17 (45.9%) observations; more often affected the bladder - in 18 (48.6%) cases. Volumes of performed operations: in 6 (16.2%) cases of complete pelvic organs evisceration, in 10 (27%) cases of MVR with rectal extirpation, in 21 (56.8%) cases of MVR with resection of the rectum and adjacent organs. More often in 27 (72.9%) patients, there was urinary tract resection, of which 11 (29.7%) patients underwent primary bladder repair with the formation of ortho- (n=3) or heterotopic (n=6) urinary reservoir of «low» pressure. Postoperative complications developed in 14 (37.8%) patients, what required re-surgery in 8 (21.6%) observed, of which urological complications occurred in 4 (10.8%) patients. Complications were not observed during the formation of the artificial bladder according to the presented method. Long-term results: RC - overall and disease-free 2-year survival - 78.1% and 65.6% respectively, PMMT - all patients are alive without signs of relapse, the timeline of observation is 24 months. Conclusion: The immediate results of MVR on locally advanced RC can be considered as satisfactory. The level of postoperative complications is primarily due to the prevalence of primary tumors. In case of urinary tract resection, primary plastic surgery is preferred. Long-term results allows to examine such operations as a method of choice in the treatment of RC with invasion in adjacent organs.